RESISTIVITY OF THE RB-SR ISOTOPIC SYSTEM OF MAGMATIC ROCKS DURING SECONDARY PROCESSES - Kostitsyn Yu.A.; Petrova A.Yu. (My University, 2004)
The resistivity of the Rb-Sr isotopic system of magmatic rocks was assayed using a fairly paradoxical approach: The examination of previously investigated metamorphosed and metasomatized rocks with disturbed isotopic systems. The following three stages of the influence of secondary processes on the Rb-Sr isotopic system are considered: (1) the presence of primary isochrons; (2) the partial disturbance of the Rb-Sr isotopic system, i.e., absence of isochrons; (3) the formation of a perfect secondary isochron. Analysis of available data shows that an metamorphic grade (up to remelting) commonly causes a partial disturbance but is not sufficient to completely reset the whole-rock Rb-Sr isotopic system. The complete isotopic reequilibration of all constituent minerals within a hand-specimen is not universally attained even via partial melting during ultrametamorphism. This suggests that an isochron sensu stricto obtained for magmatic (not metamorphic) rocks on different minerals and/or whole-rock samples corresponds to the magmatic age of the rock rather than reflecting secondary processes, whose traces are often observed in thin sections. At the worst, secondary process can destroy the whole-rock isochron without creating a new isochron. The appearance of a new mineral isochron is accompanied by apparent metamorphic transformations of the rock into crystalline schist or gneiss. The influence of the sample size on obtaining an isochron was analyzed. If the Rb-Sr isotopic system in hand-specimens of metamorphosed rocks was disturbed, it is highly improbable that a perfect isochron through an increase in the sample size up to tens and hundreds of kilograms will be obtained. Sample sizes are unimportant for the Rb-Sr analysis of fresh magmatic rocks.